Pengaruh Keefektifan Pengelolaan Pembelajaran PAK Terhadap Komitmen Moderasi Beragama Siswa Pada SMA Negeri di Kota Manado - Rogredeon Teophani Swuarzh Piri; Ellen Kambey; Jefri Mailool (PT. GIAT KONSELING NUSANTARA, 2024)
In the face of plurality and diversity that exists in the social environment, the most powerful weapon to regulate against clashes and disintegration is through moderate Religious Education. Religious Education has a significant influence to realize this. This is because religion is a guideline for mankind to have a relationship between humans and their God in accordance with the religious beliefs embraced by each person. this research leads to a type of quantitative research approach. effective management of Christian education learning and high self-efficacy can have a significant impact on increasing students' religious moderation commitment through strategies involving the use of active and elaborative learning methods, the development of a religious moderation curriculum, and the cultivation of moderation values. Good learning management supports the development of self-efficacy, and high self-efficacy strengthens commitment to the principles of religious moderation taught in Christian education. The effectiveness of Christian education and self-efficacy complement each other to shape attitudes of religious moderation. Effective Christian education can increase students' religious self-efficacy. To achieve this, Christian education learning and self-efficacy within students have an important role. A moderate attitude in religion will not be realized if Christian Education learning and learning self-efficacy do not run effectively and simultaneously